Addition of the line list for carbon disulfide to the HITRAN database: line positions, intensities, and half-widths of the 12C32S2, 32S12C34S, 32S12C33S, and 13C32S2 isotopologues. (January 2021) - Karlovets, E.V.; Gordon, I.E.; Hashemi, R.; Kochanov, R.V.; Hargreaves, R.J.; Rothman, L.S.
Highlights: A new ro-vibrational line list for the 12 C 32 S2, 32 S 12 C 34 S, 32 S 12 C 33 S, and 13 C 32 S2 isotopologues. 94992 transitions corresponding to 423 bands of four CS2 isotopologues. A unique set of spectroscopic parameters for each lower and upper state is obtained. Line positions and intensities are calculated up to J =150. Calculations of line-shape parameters are performed. Comparision with PNNL experimental spectrum between 600 and 6500 cm −1 is presented. No line list for CS2 molecule in the HITRAN2016 database. New line list will be included in the upcoming 2020 version of the HITRAN database. Abstract: A new ro-vibrational line list for the 12 C 32 S2, 32 S 12 C 34 S, 32 S 12 C 33 S, and 13 C 32 S2 isotopologues of carbon disulfide, including line positions, intensities, and linewidths, has been produced as part of the HITRAN2020 project. The carbon disulfide line list covers the range from about 0 to 6470 cm −1 (1.55 µm). The calculations of the line positions and intensities were performed by applying the PGOPHER program using a large set of measured line positions available in the literature, including the most recent high-precision dual-comb laser spectroscopy measurements and transition dipole moments for each measured band. The bands which did not have available intensity measurements were scaled to the experimental cross-sections from the PNNL database. Semi-empirical models for rotational dependence of air- and self-broadened half widths are developed based on the available experimental data. A total of 94992 transitions corresponding to 423 cold and hot bands of the 12 C 32 S2, 32 S 12 C 34 S, 32 S 12 C 33 S, and 13 C 32 S2 isotopologues up to a maximum rotational angular momentum J =150 have been calculated. The CS2 line list has been generated in HITRAN format and is provided as supplementary material and will be a part of the next edition of the HITRAN database distributed through https://www.hitran.org . This list will be useful in the fields of atmospheric environmental chemistry, medical diagnostics and planetary atmospheres. Graphical abstract: Image, graphical abstract